Efektivitas Digital Branding dalam Meningkatkan Daya Saing Produk UMKM Sambal Pecel Kanaya di Makassar - Nasir Nasir (Epsilon Journal of Management, 2026)
In today's digital era, MSME actors are required to be able to compete through the use of technology, including in building a brand image through digital branding. This study aims to analyze the effectiveness of digital branding in increasing the competitiveness of Sambal Pecel Kanaya MSME products in Makassar. The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the digital branding applied is quite effective in building a strong brand image, expanding market reach, and increasing consumer trust and buying interest. The use of social media, visual content, authentic product narratives, and customer testimonials has been proven to support increased product competitiveness. However, there are still shortcomings such as limited visual design and the lack of optimal use of other digital platforms. Therefore, it is recommended that MSMEs increase branding capacity through digital marketing training and platform diversification to strengthen the brand's position in the wider market.